A new coupled method for high-accuracy determination of fracture parameters of an interface V-notch in magneto-electro-elastic bimaterial. (December 2017) - Xu, Chenghui; Xu, Wang; Rong, Dalun; Zhou, Zhenhuan; Leung, Andrew Y.T.; Xu, Xinsheng
Highlights: A new method is introduced to the fracture analysis of V-notched MEE bimaterials. Fracture parameters and explicit solutions are obtained without any post-processing. The method shows a good reliability and high accuracy in the entire process. New results are presented and can be used as benchmarks. Abstract: A simple coupled method, called "finite element discretized symplectic method" is introduced into the mode III fracture analysis of a V-notched magneto-electro-elastic (MEE) bimaterial. High-accuracy generalized intensity factors and energy release rate are computed to evaluate the singularities of mechanical, electric and magnetic fields. The present method is carried out in two steps. In the first step, the physical domain is meshed by the conventional element for MEE media and is divided into a finite size singular region near the notch tip and a regular region far away from the notch tip. In the second step, analytical symplectic eigenfunctions are employed to transform the large number of nodal unknowns in the singular region into a small set of undetermined coefficients of a symplectic series; the nodal unknowns in the regular region remain as usual. Consequently, the computational cost is enormously reduced and fracture parameters are actually the first three coefficients of the series. Explicit expressions in the singular fields are obtained simultaneously. Numerical results are compared with the existing solutions and found to be in good agreement. Some new results are given also.